A Rare Case of Ossified Chronic Subdural Hematoma Complicated with Tension Pneumocephalus - Turgut, Mehmet; Yay, Murat Ö. (Journal of Neurological Surgery Reports, 2019)
A 59-year-old man presented with epileptic seizures interpreted as episodic syncope in the past 3 years and the patient had a history of head trauma about 4 years ago. Computed tomography revealed an ossified chronic subdural hematoma involving the right frontotemporoparietal region, which was totally resected using microsurgical technique. Postoperatively, weakness developed in right arm and magnetic resonance imaging revealed a bilateral tension pneumocephalus, which was immediately treated by a left frontal burr hole trepanation, and the patient was discharged uneventfully.
Keywords: chronic subdural hematoma; postoperative complication; tension pneumocephalus